Answer:
x = -2 and x = -3
Step-by-step explanation:
It is required to find the roots of the equation. The general quadratic equation is :
[tex]ax^2+bx+c=0[/tex]
The solution of above equation is:
[tex]x=\dfrac{-b\pm \sqrt{b^2-4ac} }{2a}[/tex]
The given equation is :
[tex]x^2+5x+6=0[/tex]
Its solutions are :
[tex]x=\dfrac{-b+ \sqrt{b^2-4ac} }{2a},\dfrac{-b- \sqrt{b^2-4ac} }{2a}[/tex]
Here, a = 1, b = 5 and c = 6
[tex]x=\dfrac{-5+ \sqrt{(5)^2-4\times 1\times 6} }{2\times 1},\dfrac{-5- \sqrt{(5)^2-4\times 1\times 6} }{2\times 1}\\\\x=-2,-3[/tex]
So, the values of x are -2 and -3. Hence, the correct option is (d).